2014
DOI: 10.1186/1824-7288-40-42
|View full text |Cite
|
Sign up to set email alerts
|

Plant sterols–enriched diet decreases small, dense LDL-cholesterol levels in children with hypercholesterolemia: a prospective study

Abstract: BackgroundSmall dense low density lipoprotein-cholesterol (sdLDL-C) molecules are more atherogenic compared with large buoyant ones. Phytosterols-enriched diets are effective in decreasing total cholesterol (TC) and low density lipoprotein-cholesterol (LDL-C) concentrations in hyperlipidemic children without significant adverse effects. Limited data on the impact of such a diet on sdLDL-C levels is available in adults while there are no reports concerning children. The purpose of this study is to prospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 26 publications
2
40
0
Order By: Relevance
“…In some studies, phytosterols and phytostanols have modestly reduced serum triglyceride levels especially in those subjects with slightly increased baseline concentrations [ 23 , 24 ]. Lipoprotein (a) concentration remains unchanged [ 9 , 25 ], and phytostanols do not affect serum proprotein convertase subtilisin/kexin type 9 concentration [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, phytosterols and phytostanols have modestly reduced serum triglyceride levels especially in those subjects with slightly increased baseline concentrations [ 23 , 24 ]. Lipoprotein (a) concentration remains unchanged [ 9 , 25 ], and phytostanols do not affect serum proprotein convertase subtilisin/kexin type 9 concentration [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, nutraceuticals and functional foods have attracted great scientific interest, with a number of clinical trials and animal studies addressing their potential role in blood lipid control and/or cardioprotection 11 . For instance, plant and fish-derived oils or fatty acids (e.g., olive oil, canola oil, n3 fatty acids, plant stanols/sterols) as well as antioxidants (e.g., polyphenols) are rigorously researched for their beneficial effects on blood lipid levels and cardiovascular health 12 13 14 15 16 .…”
mentioning
confidence: 99%
“…In another study, 59 children between 4.5-15.9 years of age were divided into 2 groups: (i) 25 subjects with a LDL-C ≥ (130 mg/dl to receive a yogurtdrink enriched with 2 g of plant sterols for 6 to 12 months (intervention group) or (ii) 34 subjects with a LDL-C < 130 mg/dl (control group). Results indicated that plant sterol consumption reduced sdLDL in the intervention group compared to the control group in which they were unchanged [45]. In a previous study, 56 healthy participants received a diet that contained high amounts of saturated fat for 2 weeks; and subsequently were randomized to one of three dietary intervention treatments; refined olive oil, rapeseed oil or sunflower oil as the principal source of fat for 4 weeks.…”
Section: Phytosterols and Vegetable Oilsmentioning
confidence: 90%